Evaluating the Causal Effects of Cash-for-Clunkers Programs in Selected Countries: Success or Failure? - Andrea Müller; Ulrich Heimeshoff (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper provides empirical evidence that Accelerated Vehicle Programs exhibit a positive influence on car registrations using unique aggregate monthly data for 23 OECD countries from 2000 to 2010. The effect is still traceable if dynamic panel data fixed effects methods are used to address the problem of unobserved heterogeneity and controlling for macroeconomic variables like industrial production, interest rate, unemployment rate and gasoline price. Furthermore our analysis reveals that passenger car sales varied considerably before the car scrappage scheme was put in place to fight the 2009 sales crisis. Compared to a simulated counterfactual situation we find a positive overall effect (until autumn 2010) of the recent Accelerated Vehicle Programs for chosen countries: the United States, South Korea, Germany and the United Kingdom. Simulation results further show that timing and duration of the policies seem much more important for its success than the budget allocated to the program.
Keywords: C33; L62; H25; 330